Study of the efficiency of the inhibitory effect of antimicrobial preparations in the production of sugar substances - Gusyatinska, Natalia; Teterina, Svitlana; Hryhorenko, Nataliia; Kalenyk, Olha (My University, 2021)
This article presents the relevance of the issue of inhibition of microbiological processes at different stages of processing of sugar-containing raw materials, in particular ensuring the microbiological purity of juices and syrups in the production of sugar sub-stances. Information on the composition of microbiota contaminating raw materials in the production of beet sugar, raw cane sugar, food syrups from sugar sorghum is analyzed.Experimental data on the evaluation of the effectiveness of a number of antimicrobial preparations in terms of growth retar-dation of pure cultures of microorganisms and the effect of disinfection during the introduction of preparations are presented.The greatest danger in production is caused by the development of spore-forming and mucus-forming bacteria, which led to the choice of research objects.Thus, the effect of antimicrobial preparations on microorganisms: mesophilic bacteria Bacillus subtilis,B. megatherium,thermophilic bacteria B. stearothermophilus, mucus-forming bacteria of the genus Leuconostos, was investigated. In addition, the effect of antimicrobials on mycelial fungi of the genus Aspergillus was studied.Based on the conducted experimental studies, the range of costs of the studied antimicrobial preparation for the suppression of contaminating microf lora in the production of sugar and food syrups from vegetable raw materials was determined.
Keywords: sugar beets; sweet sorghum juice; microbiota; effectiveness antimicrobial preparations; microbiota composition; цукрові буряки; сік солодкого сорго; мікробіота; ефективність антимікробних препаратів; склад мікробіоти; кафедра технології цукру і підготовки води; кафедра біотехнології і мікробіології